KUALITAS MIKROBIOLOGIS ES BATU BALOK BERDASARKAN CEMARAN BAKTERI Coliform DAN Salmonella sp DI WILAYAH KARANGPAWITAN, KARAWANG - Agustina, Putri; Risna, Kamelia; Wahyuningsih, Eko Sri; Gunarti, Neni Sri; Fikayuniar, Lia (Jurnal Buana Farma, 2025)
The cold temperature of ice cubes leads people to assume that ice cubes are safe for consumption without having to consider their type and quality. In reality, the cold temperature only weakens the bacteria in the ice cubes. Ice cube samples in this study were taken from the Karangpawitan area, because this area is one of the areas with many ice cube distributors, is busy, and is one of the culinary destinations for Karawang residents. The purpose of this study was to determine the quality of block ice cubes based on contamination by Coliform and Salmonella This research method includes qualitative research with an experimental approach, using the MPN test for Coliform and SSA media and gram staining for Salmonella Results from the Pondok Bogor and Kepuh locations showed positive block ice cube samples for Coliform bacteria. The Nagasari location for block ice cubes and plastic packaging tested positive for Coliform bacteria and negative for Salmonella The conclusion of this study is that the block ice cubes in the Karangpawitan area have quite high bacterial contamination. Positive results indicate that they do not meet the quality requirements based on Permenkes No. 492/Menkes/Per/IV/2010, which is >0/100 mL